The Role of Socioeconomic Factors Contributed to The Prevalence of Children under Five Years Old with Small Stature in Jatinangor - Indari, Anggie; Setiawati, Elsa Pudji; Tarigan, Rodman (Althea Medical Journal, 2015)
Background: IndonesiaÂ  is on the fifth in world population for children with small stature. It could affect to their future, so growth disorders should be detected as early as possible. The influence of growth disorders is inseparable from the socioeconomic condition of the family.Â  This study aims to analyze the influence of socioeconomic based on education, occupation and family income towards small stature children under five years old in Jatinangor.Methods: This was a study of analytic cross sectional with multi-stage proportionate consecutive sampling. 110 samples of children under five years of age (12â59months) from 12 villages (6087 children) in Jatinangor sub district were taken on October and November 2012. Their height was measured using a microtoise based on WHO Growth Chart and the socioeconomic status was measured using questionnaire completed by their motherResults: There were 32 children (29,1%) with small stature. The relationship between maternal education with short stature (p=0.310), fatherâs education with small stature (p=0.368), motherâs occupation with small stature (p=0.774), fatherâs occupation with small stature (p=0.524) and family income with small stature (p=0.890) after it was examined using chi-squre test were not significant (p>0.05).Conclusion: In Jatinangor, there are still many children with small stature under five years old and the socioeconomic factors do not have any relationship with this condition. [AMJ.2015;2(1):298â303]